Electric anode composite hydrolysis film as well as preparation method and application thereof

CN119370955AActive Publication Date: 2025-01-28GUILIN UNIV OF ELECTRONIC TECH

Patent Information

Application Number
CN202411641806.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-28
Estimated Expiration
2044-11-18

Smart Images

  • Figure CN119370955A_ABST
    Figure CN119370955A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrolysis and electrocatalytic oxidation, in particular to an electroanode composite hydrolysis membrane capable of synchronously performing hydrolysis on organophosphorus pollutants and electrocatalytic oxidation reaction on byproducts as well as a preparation method and application of the electroanode composite hydrolysis membrane. A composite conductive catalytic layer is loaded on a polyvinylidene fluoride membrane, and the composite conductive catalytic layer comprises acidized multi-walled carbon nanotubes and a zirconium-based metal organic framework with zirconium as a metal center. Meanwhile, by virtue of the characteristics of a height-adjustable topological structure, a relatively large specific surface area and high conductivity of carbon nano-particles of the metal organic framework, continuous operation of the electric anode composite hydrolysis catalytic membrane in a flow-type reactor is realized, so that the contact and oxidation efficiency of pollutants and a composite membrane interface is improved; and the problems of traditional mass transfer limitation and treatment of toxic by-products after pollutant hydrolysis are solved. The electroanode composite membrane can realize synchronous hydrolysis of organic phosphorus pollutants and degradation of toxic by-products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental materials and water treatment, and in particular to an electric anode composite hydrolysis membrane capable of simultaneously performing hydrolysis of organic phosphorus pollutants and electrocatalytic oxidation of byproducts, and a preparation method and application thereof. Background Art

[0002] As the global population grows, my country's demand for crops has also grown exponentially. In order to improve the yield and quality of agricultural products, pesticides have been widely used to protect crops from pests and diseases. As a persistent organic pollutant, pesticides often exist in water for a long time, accumulate in sediments, travel long distances and pose toxic risks to the environment, organisms and human health. Therefore, water pollution caused by pesticides has become a practical problem that needs to be solved urgently. In my country, the use of organophosphorus pesticides (OPPs) accounts for as much as 80% of the total amount of pesticides used. OPPs have high organic matter concentrations, produce a large number of intermediates and by-products during the reaction, have foul and irritating odors, and are highly toxic and difficult to biodegrade. The degradation of OPPs has become a serious global problem. Among them, Fenitrothion (FNT) is one of the common organophosphorus pesticides and is widely used in the world for insect control of crops such as cereals, cotton, rice and vegetables. It is the main component of pesticide residues in the environment. In addition to the high stability and strong polarity of the PO bond, which leads to its long-term and stable existence in water bodies, the -NO2 functional group in its structure also makes the compound resistant to traditional degradation methods. Therefore, if the organophosphorus pollutant, Fenitrothion, can be completely mineralized, it will be of great research significance.

[0003] Electrocatalytic oxidation technology has attracted much attention due to its advantages such as high efficiency, good environmental compatibility and simple operability. This method uses electrochemical reactions to produce powerful oxidants to degrade and remove various pollutants in wastewater. It is very effective in treating emerging pollutants in water sources that are difficult to remove by conventional treatment methods (such as persistent organic pollutants, drugs, pesticides, etc.). Traditional electrocatalytic oxidation technology is limited in its ability to degrade pollutants due to its poor mass transfer performance and long hydraulic residence time, and faces the problems of difficult catalyst recovery and high energy consumption. The flow-through electrocatalytic oxidation technology proposed on this basis, namely the electrocatalytic membrane coupling technology, can simultaneously realize the mineralization of organophosphorus pesticides and their toxic byproducts after degradation.

[0004] With the continuous development of electrocatalytic membrane technology, electrocatalytic membranes loaded with catalysts currently dominate this technology and can significantly increase mass transfer without losing the effective area of ​​the electrode. Metalorganic Framework (MOF), a type of compound formed by metal particles or clusters and organic ligands to form a microporous structure, has become a new generation of catalysts due to its unique structural composition, permanent porosity, high chemical stability, abundant active sites, and chemical and structural adjustability. Among them, MOF materials formed by high-valent metals (zirconium, Zr) and ligands have excellent chemical, thermal and mechanical stability, and the strong Lewis acidity of group IV metal oxygen clusters enables them to have specific hydrolysis ability for organic phosphorus pollutants. However, the inherent low conductivity of MOFs materials hinders their further application in the field of electrocatalysis. Therefore, Zr-MOF is composited with acidified multi-walled carbon nanotubes (MWCNTs), which can overcome the defect of low conductivity of traditional MOFs materials while preparing an electro-anodic composite membrane that can simultaneously hydrolyze organic phosphorus pollutants and electrocatalytic oxidation of by-products. Summary of the invention

[0005] The present invention aims to provide a method for preparing an electric anode composite membrane for simultaneously carrying out hydrolysis of organic phosphorus pollutants and electrocatalytic oxidation of byproducts and its application.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] Placing the original multi-walled carbon nanotubes in an acid solution for acidification, and obtaining acidified multi-walled carbon nanotubes after a period of time;

[0008] The polyvinylidene fluoride membrane was used as a base membrane and was soaked in a solution before use to remove the surface oxide layer;

[0009] The organic solvent, the acid solution, the metal salt and the organic ligand are mixed and stirred to obtain a metal organic framework precursor solution; the acidified multi-walled carbon nanotubes are added to the stirred metal organic framework precursor solution and stirred to obtain a composite catalyst reaction solution;

[0010] The composite catalyst reaction liquid is transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the composite electrocatalyst is obtained by heating, cooling, washing, drying and grinding;

[0011] mixing the powdered composite electrocatalyst and the solution to obtain a dispersion;

[0012] The dispersion is loaded onto the substrate membrane by suction filtration to obtain the electric anode composite hydrolysis membrane.

[0013] Preferably, the acid solution comprises nitric acid and sulfuric acid in a volume ratio of (1-6):1; the dispersion concentration of original multi-walled carbon nanotubes in the acid solution is 0.5-5 g / L; the acidification treatment is carried out under oil bath conditions at a temperature of 60-80° C. for 4-12 h.

[0014] Preferably, the pore size of the polyvinylidene fluoride base membrane is 0.22-0.45 μm; the soaking solution is 60%-99% ethanol solution; the soaking time is 1-5 hours; the flushing is to fix the polyvinylidene fluoride membrane in a vacuum filtration device and flush it with 20-80 mL of pure water for 2-6 times.

[0015] Preferably, the organic solvent is N,N-dimethylformamide (DMF); the acid solution is one of formic acid (HCOOH), acetic acid (CH3COOH), butyric acid (CH3(CH2)2COOH); the metal salt is zirconium tetrachloride (ZrCl4) or zirconium oxychloride octahydrate (ZrOCl2·8H2O); the metal ligand is one of terephthalic acid (H2BDC), trimesic acid (H3BTC), and porphyrin molecule; in the precursor solution, the volume ratio of organic solvent to acid solution is (1-2):1, and the molar ratio of metal salt to organic ligand is (1-4):1; the stirring time is 0.5-1h.

[0016] Preferably, the mass of the added acidified multi-walled carbon nanotubes is 10 to 50 mg; and the stirring time is 1 to 4 hours.

[0017] Preferably, the heating temperature is 110-150°C, and the time is 12-48 hours; the cooling time is 6-12 hours; the washing solution is 30-60 mL DMF, 70-100 mL methanol and 140-170 mL pure water for washing 2-3 times in sequence; the drying temperature is 60-80°C, and the time is 8-12 hours; and after grinding, the product is sieved through a 200-400 mesh sieve.

[0018] Preferably, the solution of the dispersion is a 60% to 99% ethanol solution; the ratio of the catalyst to the solution in the dispersion is (10 to 50) mg: (20 to 80) mL.

[0019] Preferably, the mass ratio of the acidified multi-walled carbon nanotubes to the zirconium-based metal organic framework in the composite electrocatalyst is 1:(1-5).

[0020] Preferably, the electric anode composite hydrolysis membrane is used in a continuous flow system to remove organic phosphorus pollutants in wastewater.

[0021] Preferably, the organic phosphorus pollutant is fenitrothion; and the pollutant-containing influent water comprises sodium sulfate electrolyte with a concentration of 50 mM.

[0022] The present invention provides a method for preparing an electric anode composite membrane for simultaneously hydrolyzing organic phosphorus pollutants and electrocatalytic oxidation of byproducts, comprising the following steps: placing original multi-walled carbon nanotubes in an acid solution, performing an acidification treatment, and obtaining acidified multi-walled carbon nanotubes after a period of time; using a polyvinylidene fluoride membrane as a base membrane, soaking it in a solution before use and then rinsing it to remove the surface oxide layer; mixing an organic solvent, an acid solution, a metal salt and an organic ligand, and stirring them evenly to obtain a metal organic framework precursor solution; adding the acidified multi-walled carbon nanotubes to the stirred metal organic framework precursor solution, and stirring them thoroughly to obtain a composite catalyst reaction liquid; transferring the composite catalyst reaction liquid to a stainless steel reactor lined with polytetrafluoroethylene, heating, cooling, washing, drying, and grinding to obtain a composite electrocatalyst; mixing a powdered composite electrocatalyst with a solution to obtain a dispersion; and loading the dispersion onto a base membrane by suction filtration to obtain the electric anode composite hydrolysis membrane. The present invention first prepares a composite electrocatalyst, and then forms an alkaline film directly on the surface of the base membrane with a dispersion, which is simple and efficient to operate. In the examples, the degradation and mineralization capabilities of the electro-anodic composite hydrolysis membrane provided by the present invention on organophosphorus pesticides and their toxic byproducts were studied by comparing hydrolysis experiments and electrocatalytic oxidation experiments in a continuous flow operation mode. The results show that the electro-anodic composite hydrolysis membrane can achieve simultaneous mineralization and removal of organophosphorus pesticides and their toxic byproducts under electrocatalytic conditions while improving the degradation of organophosphorus pesticides. In addition, the electrocatalytic oxidation experiment on antibiotics in the examples further proves that the electro-anodic composite membrane hydrolysis membrane still has a high removal rate for organic pollutants other than organophosphorus. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope image of the multi-walled carbon nanotubes after acidification in Example 1;

[0024] Figure 2 This is a scanning electron microscope image of MOF-808 in Comparative Example 1;

[0025] Figure 3 This is an electron microscope image of the electric anode composite hydrolysis membrane (MOF-808@CNT / PVDF) in Example 1;

[0026] Figure 4 XRD diagrams of the acidified multi-walled carbon nanotubes, MOF-808 and composite electrocatalyst (MOF-808@CNT) in Example 1 and Comparative Example 1;

[0027] Figure 5 It is a comparison diagram of the degradation and hydrolysis curves of 15 mg / L fenitrothion by the electric anode composite hydrolysis membrane in Example 1 and the MOF-808 hydrolysis membrane in Comparative Example 1;

[0028] Figure 6This is a comparison chart of the degradation and hydrolysis curves of 15 mg / L 4-nitro-meta-cresol by the electric anode composite hydrolysis membrane in Example 1 and the MOF-808 hydrolysis membrane in Comparative Example 1;

[0029] Figure 7 It is a comparison diagram of the degradation and hydrolysis curves of 15 mg / L oxytetracycline by the electric anode composite hydrolysis membrane in Example 1 and the MOF-808 hydrolysis membrane in Comparative Example 1;

[0030] Figure 8 This is a comparison chart of the hydrolysis of 15 mg / L of fenitrothion, 4-nitro-meta-cresol and oxytetracycline by the MOF-808 hydrolysis membrane in Comparative Example 1. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing an electric anode composite membrane, comprising the following steps:

[0032] Placing the original multi-walled carbon nanotubes in an acid solution for acidification, and obtaining acidified multi-walled carbon nanotubes after a period of time;

[0033] The polyvinylidene fluoride membrane is used as a base membrane and is soaked and rinsed in a solution before use to remove the surface oxide layer;

[0034] The organic solvent, the acid solution, the metal salt and the organic ligand are mixed and stirred to obtain a metal organic framework precursor solution; the acidified multi-walled carbon nanotubes are added to the stirred metal organic framework precursor solution and stirred to obtain a composite catalyst reaction solution;

[0035] The composite catalyst reaction liquid is transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the composite electrocatalyst is obtained by heating, cooling, washing, drying and grinding;

[0036] mixing the powdered composite electrocatalyst and the solution to obtain a dispersion;

[0037] The dispersion is loaded onto the substrate membrane by suction filtration to obtain the electric anode composite hydrolysis membrane.

[0038] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.

[0039] The present invention provides a composite electrocatalyst, which is obtained by compounding acidified multi-walled carbon nanotubes and zirconium-based metal organic frameworks. In the present invention, the diameter of the zirconium-based metal organic framework is preferably 400-500nm. In the present invention, the preparation method of the composite electrocatalyst preferably comprises the following steps: mixing acidified multi-walled carbon nanotubes, zirconium oxychloride octahydrate, trimesic acid, N,N-dimethylformamide and formic acid, preferably mixing zirconium oxychloride octahydrate, trimesic acid, N,N-dimethylformamide and formic acid, and then adding acidified multi-walled carbon nanotubes to the resulting mixture. In the present invention, the acid solution ratio of the multi-walled carbon nanotubes acidified is (1-6):1, more preferably 3:1; the original multi-walled carbon nanotube dispersion concentration in the acid solution is 0.5-5g / L, more preferably 1g / L; the acidified oil bath temperature is 60-80°C, more preferably 80°C; the acidified oil bath time is 4-12h, more preferably 4h. In the present invention, the volume ratio of the organic solvent to the acid solution in the metal organic framework precursor solution is (1-3):1, more preferably 1:1; the metal salt is preferably zirconium oxychloride octahydrate; the organic ligand is preferably trimesic acid; the molar ratio of zirconium oxychloride octahydrate to trimesic acid is (1-4):1, more preferably 3:1; the stirring time of the precursor solution is 0.5-1h, more preferably 0.5h. In the present invention, the mass of the acidified multi-walled carbon nanotubes added to the precursor solution is 10-50mg, more preferably 50mg; the stirring time after the addition is 1-4h, more preferably 2.5h.

[0040] After obtaining the composite electrocatalyst mixed solution, the composite electrocatalyst of the present invention is synthesized by a one-pot hydrothermal method, wherein the hydrothermal heating temperature is 110-150°C, more preferably 130°C; the hydrothermal time is 12-48h, more preferably 24h; the cooling time is 6-12h, more preferably 12h. The present invention washes with organic solvent and pure water to elute the excess organic ligand and acid solution in the synthesis process of the composite electrocatalyst, wherein the washing solution is more preferably 40mL DMF, 80mL methanol and 150mL pure water respectively; the drying temperature and time are more preferably 80°C drying for 12h; the mass ratio of the synthesized multi-walled carbon nanotubes to MOF-808 after acidification of the composite electrocatalyst is preferably 1:5.

[0041] In the present invention, the composite electrocatalyst is a composite catalyst material synthesized by a one-pot hydrothermal method of acidified multi-walled carbon nanotubes and a zirconium-based metal organic framework. The present invention combines the metal Zr of the zirconium-based metal organic framework MOF-808 formed by octahydrate zirconium oxychloride and an organic ligand trimesic acid with the surface carboxyl groups of the acidified multi-walled carbon nanotubes through chemical bonds to form a composite material. The introduction of multi-walled carbon nanotubes overcomes the inherent low conductivity defect of MOF materials, and at the same time, the advantages of large specific surface area and permanent porosity of MOF materials improve the hydrophilicity of carbon nanotubes to a certain extent.

[0042] The composite electrocatalyst powder obtained by the present invention does not need to be subsequently modified, and the composite electrocatalyst is formed on the surface of the substrate membrane to obtain a composite electro-anodic oxidation hydrolysis membrane. In the present invention, the substrate membrane is preferably a polyvinylidene fluoride (PVDF) membrane, and the pore size of the substrate membrane is 0.22 to 0.45 μm, and more preferably 0.45 μm. In the present invention, the substrate membrane needs to be soaked before use, and the soaking solution is preferably a 99% ethanol solution. In the present invention, the film-forming method is preferably suction filtration film-forming, specifically, the composite electrocatalyst powder is dispersed in an ethanol solution preferably of 99%, preferably the ratio of catalyst to solution is 30 mg: 60 mL, the dispersion is placed on a single side of the substrate membrane for suction filtration, the dispersion is formed into a wet film on a single side of the substrate membrane, and then dried to form a functional film on a single side of the substrate membrane to obtain a composite electrocatalytic anode hydrolysis membrane. In the present invention, the suction filtration is preferably vacuum filtration; the drying is preferably vacuum drying, 80 ° C, 12h.

[0043] The present invention provides an electric anode hydrolysis composite membrane prepared by the preparation method described in the above technical solution, including a base film and a functional film loaded on the surface of the base film; the functional film is formed by a composite zirconium-based metal organic framework (MOF-808) and acidified multi-walled carbon nanotubes. In the present invention, specifically, zirconium oxychloride octahydrate, organic ligand trimesic acid and acidified multi-walled carbon nanotubes are formed in one step through a one-pot hydrothermal method to obtain a composite electrocatalyst (MOF-808@CNT). The functional film of MOF-808 composite acidified multi-walled carbon nanotubes provided by the present invention is stably loaded on the surface of the base film, and the functional film does not have obvious shedding phenomenon during multiple cycles of use.

[0044] The present invention provides the application of the electro-anodic composite hydrolysis membrane described in the above scheme in the electro-catalytic oxidation degradation of organophosphorus pesticide (fenthion) and its byproduct 4-nitro-meta-cresol (3M4NP). In the present invention, the electro-anodic composite hydrolysis membrane can be preferably used as an electro-anodic filter membrane in the field of sewage treatment, which is convenient for recycling and reuse. It is more environmentally friendly, stable, efficient and energy-saving during use, and can achieve continuous operation, solving the problem that traditional granular powder catalysts are difficult to recycle and reuse after use.

[0045] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] 160 mg of multi-walled carbon nanotubes, 120 mL of concentrated nitric acid and 40 mL of concentrated sulfuric acid were added to a 250 mL round-bottom flask, a rotor was placed, and ultrasonication was performed for 30 min. After the ultrasonication was completed, the round-bottom flask was transferred to an oil bath and stirred at 80°C for 4 h. After the reaction was completed, the obtained black suspension was repeatedly washed to neutrality by vacuum filtration, and the acidified multi-walled carbon nanotube powder was collected and vacuum dried at 80°C for 12 h to obtain the acidified multi-walled carbon nanotubes.

[0048] 0.48 g of zirconium oxychloride octahydrate and 0.10 g of trimesic acid were added to a 60 mL mixture consisting of 30 mL of N,N-dimethylformamide and 30 mL of formic acid, and stirred at room temperature (25 °C) for 0.5 h to obtain a clear and transparent MOF-808 precursor solution;

[0049] 50 mg of acidified multi-walled carbon nanotubes were added to the MOF-808 precursor solution and stirred at room temperature (25°C) for 2.5 h to obtain a composite electrocatalyst reaction solution;

[0050] The composite electrocatalyst reaction solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in an oven at 130°C for 24 hours, and cooled naturally to room temperature for 12 hours after the reaction. The obtained gray-black suspension was filtered through a vacuum filtration device and washed with 40 mL N,N-dimethylformamide, 80 mL methanol and 150 mL pure water in sequence to wash away the excess acid and organic solvent during the reaction. The gray-black powder was collected and vacuum dried at 80°C for 12 hours to obtain a composite electrocatalyst, recorded as MOF-808@CNT;

[0051] 30 mg of the composite electrocatalyst was dispersed in 60 mL of ethanol solution to obtain a composite electrocatalyst dispersion. The composite electrocatalyst dispersion was placed on one side of a polyvinylidene fluoride membrane (pore size 0.45 μm) for vacuum filtration, and the composite electrocatalyst formed a functional film on one side of the polyvinylidene fluoride membrane to obtain an electric anode composite hydrolysis membrane (MOF-808@CNT / PVDF).

[0052] Comparative Example 1

[0053] The MOF-808 hydrolysis membrane was prepared according to the method of Example 1, except that the steps of acidifying the multi-walled carbon nanotubes and adding the multi-walled carbon nanotubes after acidification were omitted.

[0054] 0.48 g of zirconium oxychloride octahydrate and 0.10 g of trimesic acid were added to a 60 mL mixture consisting of 30 mL of N,N-dimethylformamide and 30 mL of formic acid, and stirred at room temperature (25 °C) for 0.5 h to obtain a clear and transparent MOF-808 precursor solution;

[0055] The MOF-808 precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in an oven at 130°C for 24 hours, and cooled naturally to room temperature for 12 hours after the reaction. The obtained gray-black suspension was filtered through a vacuum filtration device and washed with 40 mL N,N-dimethylformamide, 80 mL methanol and 150 mL pure water in sequence to wash away the excess acid and organic solvent during the reaction. The gray-black powder was collected and vacuum dried at 80°C for 12 hours to obtain a composite electrocatalyst, recorded as MOF-808;

[0056] Figure 1 This is a scanning electron microscope image of multi-walled carbon nanotubes after acidification. Figure 1 It can be seen that the morphology of multi-walled carbon nanotubes after acid treatment is not destroyed.

[0057] Figure 2 This is a scanning electron microscope image of MOF-808. Figure 2 It can be seen that the MOF-808 crystal phase appears and the material is successfully prepared.

[0058] Figure 3 This is an electron microscope image of the anode composite hydrolysis membrane (MOF-808@CNT / PVDF). Figure 3 It can be seen that MOF-808 was successfully loaded on the surface of acidified multi-walled carbon nanotubes through a one-pot hydrothermal method, and the composite electrocatalyst (MOF-808@CNT) was successfully prepared.

[0059] Figure 4 XRD patterns of MOF-808, acidified multi-walled carbon nanotubes and composite electrocatalyst (MOF-808@CNT). Figure 4It can be seen that the synthesized MOF-808 presents satellite peaks accompanied by significant peaks in the XRD diagram, and the XRD spectrum shows obvious diffraction peaks, which confirms the crystal structure of MOF and proves that the composite of MOF-808 and acidified multi-walled carbon nanotubes does not change the structure of the two materials.

[0060] The performance tests of the membrane materials prepared in Example 1 and Comparative Example 1 were carried out as follows:

[0061] (1) Electrolysis experiment

[0062] 50mL of 15mg / L fenitrothion solution, 15mg / L 4-nitro-meta-cresol and 15mg / L oxytetracycline solution were prepared respectively, and the three solutions were all supported by sodium sulfate solution with a concentration of 50mM / L. Using the electric anode composite hydrolysis membrane in Example 1 as anode, Ti mesh as cathode, cathode on top, anode below, and the vertical spacing of the two was 5mm, fixed in the device of circulating filtration. Peristaltic pump provides a flow velocity of 3mL / min, and the electrocatalytic oxidation experiment uses a DC power supply to provide a constant voltage of 3V, and the cycle rate is degraded for 60min in the device. During the degradation process, sampling is performed at different times for concentration analysis, and the degradation efficiency of the electric anode composite hydrolysis membrane to different pollutant solutions in Example 1 is calculated according to the concentration change.

[0063] (2) Hydrolysis experiment

[0064] 50 mL of 15 mg / L cypermethrin solution, 15 mg / L 4-nitro-meta-cresol and 15 mg / L oxytetracycline solution were prepared respectively, as control variables, and the three solutions were consistent with the electrolysis experiment, with a sodium sulfate solution with a concentration of 50 mM / L as the supporting electrolyte. The MOF-808 hydrolysis membrane in Comparative Example 1 was fixed in a circulating filtration device, and a peristaltic pump provided a flow rate of 3 mL / min. The peristaltic pump was used to circulate and filter in the device for 60 min. During the hydrolysis process, samples were taken at different times for concentration analysis, and the hydrolysis rate of the MOF-808 hydrolysis membrane in Comparative Example 1 for different pollutant solutions was calculated according to the concentration change.

[0065] Figure 5 The degradation and hydrolysis curves of 15 mg / L fenitrothion by the electric anode composite hydrolysis membrane in Example 1 and the MOF-808 hydrolysis membrane in Comparative Example 1 are compared. Figure 5 It can be seen that the MOF-808 hydrolysis membrane has a certain hydrolysis ability for cypermethrin; the electrolysis experiment carried out after MOF-808 was composited with multi-walled carbon nanotubes after acidification showed that the degradation of cypermethrin by the electric anode composite hydrolysis membrane was significantly improved on the original hydrolysis ability.

[0066] Figure 6The degradation and hydrolysis curves of 15 mg / L 4-nitro-meta-cresol, a byproduct of fenitrothion, by the electric anode composite hydrolysis membrane in Example 1 and the MOF-808 hydrolysis membrane in Comparative Example 1 are compared. Figure 6 It can be seen that the MOF-808 hydrolysis membrane has basically no hydrolysis ability for 4-nitro-meta-cresol; while the electro-anodic composite hydrolysis membrane used in the electrolysis experiment has a higher degradation ability for 4-nitro-meta-cresol, and at the same time proves that the electro-anodic composite membrane of the present invention can simultaneously degrade fenitrothion and its by-product 4-nitro-meta-cresol.

[0067] Figure 7 The degradation and hydrolysis curves of 15 mg / L oxytetracycline by the electric anode composite hydrolysis membrane in Example 1 and the MOF-808 hydrolysis membrane in Comparative Example 1 are compared. Figure 7 It can be seen that the MOF-808 hydrolysis membrane has basically no hydrolysis ability for oxytetracycline; while the electro-anodic composite hydrolysis membrane in the electrolysis experiment has a high degradation ability for oxytetracycline, proving that the electro-anodic composite membrane in the present invention has a certain degradation ability for various types of organic pollutants.

[0068] Figure 8 The comparison chart of the hydrolysis of 15 mg / L of fenitrothion, 4-nitro-meta-cresol and oxytetracycline by MOF-808 hydrolysis membrane in Comparative Example 1 is shown in FIG. Figure 8 It can be seen that the MOF-808 hydrolysis membrane has a high hydrolysis ability only for the fenitrothion solution, thus proving the specific hydrolysis ability of MOF-808 for organophosphorus pollutants.

[0069] In summary, the test examples have proved that the electric anode composite hydrolysis membrane (MOF-808@CNT / PVDF) provided by the present invention has a certain degree of specificity for the hydrolysis of organic phosphorus pollutants, and can degrade the toxic by-products of organic phosphorus pollutants, and has a high degradation efficiency for various types of organic pollutants; the preparation method of the electric anode composite hydrolysis membrane provided by the present invention is simple, easy to recover the catalyst, and there is no obvious shedding after multiple uses.

[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An electric anode composite hydrolysis membrane, characterized in that: The invention comprises a substrate film and a composite electrocatalyst which are stacked in sequence. The composite electrocatalyst is an acidified carbon nanotube with an octahedral cubic zirconium-based metal organic framework loaded on the surface.

2. The electric anode composite hydrolysis membrane according to claim 1, characterized in that: The particle size of the zirconium-based metal organic framework in the electrocatalytic layer is 400-500nm.

3. A method for preparing an electric anode composite hydrolysis membrane, characterized in that: The preparation method comprises the following steps: Placing the original multi-walled carbon nanotubes in an acid solution for acidification, and obtaining acidified multi-walled carbon nanotubes after a period of time; The polyvinylidene fluoride membrane was used as a base membrane and was soaked in a solution before use to remove the surface oxide layer; The organic solvent, the acid solution, the metal salt and the organic ligand are mixed and stirred to obtain a metal organic framework precursor solution; the acidified multi-walled carbon nanotubes are added to the stirred metal organic framework precursor solution and stirred to obtain a composite catalyst reaction solution; The composite catalyst reaction liquid is transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the composite electrocatalyst is obtained by heating, cooling, washing, drying and grinding; mixing the powdered composite electrocatalyst and the solution to obtain a dispersion; The dispersion is loaded onto the substrate membrane by suction filtration to obtain the electric anode composite hydrolysis membrane.

4. The preparation method according to claim 3, characterized in that: The acid solution includes nitric acid and sulfuric acid in a volume ratio of (1-6):1; the dispersion concentration of the original multi-walled carbon nanotubes in the acid solution is 0.5-5 g / L; the acidification treatment is carried out under oil bath conditions at a temperature of 60-80° C. for 4-12 hours.

5. The preparation method according to claim 3, characterized in that: The pore size of the polyvinylidene fluoride base membrane is 0.22-0.45 μm; the soaking solution is 60%-99% ethanol solution; the soaking time is 1-5 hours; the flushing is to fix the polyvinylidene fluoride membrane in a vacuum filtration device and flush it with 20-80 mL of pure water for 2-6 times.

6. The preparation method according to claim 3, characterized in that: The organic solvent is N,N-dimethylformamide (DMF); the acid solution is one of formic acid (HCOOH), acetic acid (CH3COOH), and butyric acid (CH3(CH2)2COOH); the metal salt is zirconium tetrachloride (ZrCl4) or zirconium oxychloride octahydrate (ZrOCl2·8H2O); the metal ligand is terephthalic acid (H2BDC) or trimesic acid (H3BTC); in the precursor solution, the volume ratio of the organic solvent to the acid solution is (1-3):1, and the molar ratio of the metal salt to the organic ligand is (1-4):1; the stirring time is 0.5-1h; the mass of the added acidified multi-walled carbon nanotubes is 10-50mg; and the stirring time is 1-4h.

7. The preparation method according to claim 3, characterized in that: The heating temperature is 110-150° C., and the time is 12-48 hours; the cooling time is 6-12 hours; the washing solution is 30-60 mL DMF, 70-100 mL methanol and 140-170 mL pure water for washing 2-3 times in sequence; the drying temperature is 60-80° C., and the time is 8-12 hours; and after grinding, the mixture is sieved through a 200-400 mesh sieve.

8. The preparation method according to claim 3, characterized in that: The solution of the dispersion liquid is 60% to 99% ethanol solution; the ratio of the catalyst to the solution in the dispersion liquid is (10 to 50) mg: (20 to 80) mL.

9. The preparation method according to claim 3, characterized in that: The mass ratio of the acidified multi-walled carbon nanotubes to the zirconium-based metal organic framework in the composite electrocatalyst is 1:(1-5).

10. An application of the electric anode composite hydrolysis membrane according to claim 1 or 2 in a continuous flow system for removing organic phosphorus pollutants in wastewater, characterized in that: The organic phosphorus pollutant is fenitrothion; the pollutant-containing influent water includes sodium sulfate electrolyte with a concentration of 50 mM.

Citation Information

Patent Citations

  • Method for preparing membrane electrode based on carbon nanotubes and electrolytic removal method of organic pollutants with membrane electrode

    CN104211138A

  • Electrocatalysis membrane filter device and preparation method of electrocatalysis filtration membrane of device

    CN108543423A

  • Preparation method and application of bifunctional photoelectrochemical composite membrane

    CN110711500A

  • Oxidordeuctase electrode and enzyme electric reactor used for enzyme electric catalytic reduction, and preparation method of oxidordeuctase electrode

    CN112708612A

  • Electro-Fenton composite membrane as well as preparation method and application thereof

    CN117819675A

Cited By

  • Water pollution treatment equipment and method suitable for industrial high-fluorine wastewater

    CN120736611A

  • Water pollution treatment equipment and method suitable for industrial high-fluorine wastewater

    CN120736611B